An annotated checklist of the oryctine rhinoceros beetles (Coleoptera: Scarabaeidae: Dynastinae: Oryctini) of the Neotropical and Nearctic realms - Gasca-Álvarez, Héctor Jaime; Ratcliffe, Brett C. (Zootaxa, 2011)
A brief review of the taxonomy and natural history of the New World Oryctini is provided. An updated and annotated checklist of the Oryctini of the Neotropical and Nearctic realms is included. This now includes 14 genera, 133 extant species, and two extinct species. Tehuacania porioni Dechambre, 2009 (Oryctini) is reduced to synonymy with Barutus hartmanni Ratcliffe, 2003 (Pentodontini).